Use of Invertible Rapid Transform in Motion Analysis - Gamec, J.; Turan, J. (Radioengineering Society, 1996)
The paper presents the results of a study on the use of invertible rapid transform for the motion estimation in a sequence of images. Novel motion estimation algorithms based on the analysis of the matrix of states (or matrices of states) of the invertible rapid transform are described. Experimental results with proposed algorithms are presented and compared with the well-known 2D-log method in real image sequences.
Keywords: motion estimation; rapid transform; invertible rapid transform